INFLUENCE ОF SОIL FERTILIZATIОN SYSTEMS ОN SОIL CHARACTERISTICS FOR A MОNОCULTURE ОF SUNFLОWER - ОANA-MARIA MUSCALU PLESCAN; FLORIN-MARIAN NEDEFF; ELENA PARTAL; EMILIAN MOSNEGUTU; MIRELA PANAINTE-LEHADUS; OANA IRIMIA; CLAUDIA TOMOZEI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The purpose of this research has been to determine the influence of soil fertilizations systems (fertilization with: nitrogen, phosphorus, nitrogen and phosphorus, farmyard manure) on some soil characteristics humidity, pH and content in: lead, cadmium, calcium, iron). The experiments have been carried out in the experimental field of National Agricultural Research and Development Institute – Fundulea, Romania, for a sunflower monoculture. The lowest values of the metal content in sоil (lead) have been recorded for sunflower experimental variants – fertilized with farmyard manure (2.18 mg∙kg-1 d.m.). Calcium has the highest content in sоil (4712 mg∙kg-1 d.m., 15-30 cm working depth) in case of the sоil control sample.